1998
DOI: 10.1007/s003830050477
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative intussusception after surgery for malrotation and appendicectomy in a newborn

Abstract: Postoperative intussusception in the newborn is an infrequent condition. A 17-day-old female with duodenal stenosis and malrotation underwent excision of the membrane in the duodenum and incidental appendicectomy. Postoperatively, a ceco-colic type of intussusception occurred, necessitating a right hemicolectomy. We speculate that the causative factors are twofolds: the embedded appendiceal stump, a polyp-like protrusion that became a lead point, and the non-fixation of the ileocecal mesentery, which facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Almost all the reported cases of Waugh syndrome have an ileocecal intussusception. Tatekawa et al [4] reported that the mobile cecum associated with malrotation may be the contributing factor for development of ileocecal intussusception. Our case demonstrated the very rare occurrence of a colocolic intussusception in a malrotated intestine where the lead point was an intestinal lymphangioma, the first reported case in the English literature.…”
Section: Discussionmentioning
confidence: 98%
“…Almost all the reported cases of Waugh syndrome have an ileocecal intussusception. Tatekawa et al [4] reported that the mobile cecum associated with malrotation may be the contributing factor for development of ileocecal intussusception. Our case demonstrated the very rare occurrence of a colocolic intussusception in a malrotated intestine where the lead point was an intestinal lymphangioma, the first reported case in the English literature.…”
Section: Discussionmentioning
confidence: 98%
“…3,4 Tatekewa et al 3 suggested that the mobile cecum is associated with malrotation, which suspected to be factor allowing the terminal ileum to pass into the distal colon. Kidd et al 4 found 7 postoperative intussusception cases after the Ladd procedure in a large institutional series and suggested that the Ladd procedure predisposes children to postoperative intussusception.…”
Section: Discussionmentioning
confidence: 99%
“…Plausible theories include local spasm or edema of the bowel wall, prolonged anesthesia with electrolyte imbalance, abnormal postoperative peristalsis, chemotherapy, radiation and bowel ischemia. 4 , 5 , 7 Potential leading points may be the anastomotic suture line, an appendiceal stump or the presence of intestinal tubes. 5 , 6 , 7 , 8 The etiology of intussusception following appendectomy is, however, not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…4 , 5 , 7 Potential leading points may be the anastomotic suture line, an appendiceal stump or the presence of intestinal tubes. 5 , 6 , 7 , 8 The etiology of intussusception following appendectomy is, however, not completely understood. Invagination of the stump may be associated with a small abscess which in turn may act as a lead point of intussusception, 9 but cases of cecocolic intussusception have been reported in which the stump was not inverted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation